Assessment of Environmental Flow Requirements for Four Major Chinese Carps in the Lower Reaches of the Jinsha River, Southwest China - Dai, Lingquan; Wang, Yu; Dai, Huichao; Li, Wei; Zheng, Tiegang; Zhang, Qingsen (Frontiers in Ecology and Evolution, 2022)
An appropriate environmental flow (AEF) is one of the necessary conditions for fish spawning. The operation of cascade reservoirs in the lower reaches of the Jinsha River has changed the discharge process downstream, which in turn has directly affected the spawning habitat of fishes. Determining how to quantitatively evaluate the impact of different outflows from Xiangjiaba Reservoir on the spawning habitat of four major Chinese carp species in the downstream area is a key problem that must be solved immediately. The Yibin River section was selected as the study area, and the velocity and water depth were measured. A physical habitat simulation model (PHABSIM) was used to analyze the main hydrodynamic conditions that affect the spawning of the four major Chinese carp species and to quantify the weighted usable area (WUA) for the fishes based on different outflows from Xiangjiaba Reservoir. Hydrodynamic suitability curves for the four major Chinese carp species were established based on observed data from 2012 to 2020, and a two-dimensional hydrodynamic model was developed using a triangular grid to obtain the hydrodynamic distribution characteristics of the fish habitat. Then, the AEF range was obtained based on the outflow-WUA relationship. The results showed that the velocity during the spawning period was 0.6–1.3 m/s, the most appropriate velocity was 0.9–1.0 m/s, the water depth range was 3.0–18.0 m, and the most appropriate water depth was 9.0–12.0 m. Additionally, the AEF range was 2,000–4,500 m3/s, and the optimal AEF was, m3/s. The research results provide a scientific basis for the ecological operation of cascade reservoirs in the lower reaches of the Jinsha River.